Chronic eosinophilic pneumonia: a paediatric case. (25th April 2013) - Tassinari, Davide; Di Silverio Carulli, Chiara; Visciotti, Francesca; Petrucci, Roberta
Abstract : Chronic eosinophilic pneumonia (CEP) is a rare disorder in children, characterised by respiratory and systemic symptoms, with a generally good prognosis. A 11-year-old asthmatic girl was admitted to our clinic with a 3-month history of progressive cough, dyspnoea, weight loss and asthenia. Peripheral blood eosinophilia, multiple bilateral pulmonary infiltrates to the x-ray, multiple nodules with a surrounding ground-glass halo and peripheral predominance to the chest CT suggested the diagnosis of eosinophilic lung disease (ELD). Further investigations ruled out other ELD and supported diagnosis of CEP. The response to oral corticosteroids was dramatic, no relapses were reported in 2-year follow-up while the patient was under inhaled corticosteroids for pre-existing asthma.